PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII - Nabila, Vania Putri (Jurnal Edukasi dan Penelitian Matematika, 2023)
The part the most important purpose of mathematics learning was understood the concepts of mathematical. However, based on the tests results conducted in class VIII SMPN 4 Bukittinggi, it showed that concepts understanding of students' in mathematical was still relatively low. One of the strategies implemented by educators to increase concepts understanding of students' in mathematical is the model by learning in cooperative of the Connecting, Organizing, Reflecting, Extending type. This research purpose to find out and describe the concepts understanding of students' in mathematical who study with the type by model of learning in cooperative of  the Connecting, Organizing, Reflecting, Extending type is more goog than students who learn with the learning in direct model in class VIII SMPN 4 Bukittinggi. The research type used was a Quasi Experiment with a non-equivalent posttest-only control group design. The research population population were class VIII SMPN 4 Bukittinggi with samples from class VIII C and VIII E. The instrument research used was a concepts understanding of students test in consist of questions in essay which were analyzed by testing the hypothesis used the test by Mann Whitney. Thus we got conclusion that the concepts understanding of students' in mathematical who studied with the learning in cooperative model of the Connecting, Organizing, Reflecting, Extending type was more good than students who studied with the learning in direct model in class VIII SMPN 4 Bukittinggi. Keywords– Cooperative, CORE, mathematical concepts